Contouring the emergence profile of peri-implant soft tissue by provisionals on implants: Case report - Lazić Vojkan; Todorović Ana; Đorđević Igor; Milošević Nataša; Popović Danica; Miletić Ana (Serbian Medical Society - Dental Section, Belgrade, 2015)
Aesthetic outcome of implant therapy involves the appropriate architecture of peri-implant soft tissue and interdental papilla. The dynamic compression technique of soft tissue is mentioned in contemporary literature as one of the methods for achieving optimal emergence profile. The aim of this case report was to present soft tissue prosthetic modeling with temporary crowns on implants for obtaining an emergence profile of final restoration. A 25-year-old female patient with missing left maxillary central incisor was referred to the Department of Oral Surgery School of Dental Medicine University in Belgrade for dental implant placement. After detailed planning, implant placement of Straumann Bone level implant NC O 3, 3×12 mm (StraumannR Bone Level NC), in the position of 21 was performed. Upon completion of osseointegration period, screw retained laboratory temporary crown was fabricated. During the next 3 months emergence profile was scalloped by creating additional pressure on the soft tissue with periodic adding the composite resin material to a temporary crown. The created emergence profile was transferred to the master cast by using customized impression coping, making possible fabrication of the final implant restoration according to the design made with provisional restoration. Soft tissue conditioning using temporary dental restorations on implants presents a non-invasive method with predictable aesthetic result.